Grain size dependent distribution of different plastic types in coarse shredded mixed commercial and municipal waste. (15th February 2020) - Möllnitz, S.; Khodier, K.; Pomberger, R.; Sarc, R.
Highlights: Plastic potential and types in commercial and municipal waste are investigated. Plastic type by using NIR-sensor and a FTIR-spectrometer is analysed. Dimension specific (2D & 3D) plastic distribution in different grain sizes is shown. Identification of grain sizes for targeted practical removal of valuable plastics. Grain size dependent sorting supports material recycling and circular economy. Abstract: The Waste Framework Directive regulates the recycling of waste in Europe. The definition of waste is specified in different guidelines and regulations. Mixed Commercial Waste is waste from industry which is not collected separately. Currently there is little known about its composition. Mixed Municipal Waste, on the other hand, is household waste that cannot be attributed to any separately collected waste fraction (AdSLR, 2012). Both wastes are currently treated focussing on the generation of refuse-derived fuel rather than on the separation of recyclables (mainly performed for metals). The purpose of this paper is to characterise the amounts of various plastic types contained in different grain sizes of two-dimensional and three-dimensional plastics sorting fractions of both waste types. Nine types of plastics were identified as potential recycling materials for which recycling processes as well as a market are available. Both wastes were shredded, sampled and sieved into nine grain size classes (GSC). Fractions coarser than 20 mm were sorted, generating a 'plastics-2D' and a 'plastics-3D' fraction among others. The two plastics fractions were further characterised as plastic types using a near-infrared sensor and a Fourier-transform infrared spectrometer. The results reveal a potential for plastic recycling through mechanical and feedstock recycling options for the examined wastes. Certain types of plastics, of certain dimensionality, tend to come in certain grain sizes, which is essential for mechanical enrichment and discharge.